Los Derechos Humanos Del Pueblo, Ante Una Pandemia Como El Covid-19, Desde Una Óptica Jurídica (Global Journal of Human-Social Science, 2022)
The objective of the investigation was: to determine the human rights of the people, in the fase of a pandemic such as Covid-19, as well as the obligation of a Nation in the fase of a phenomenon of this nature, relating the three variables, to establish whether there is a right or not, to compensation in case of death, for the relatives in charge of the State, the methodology used was qualitative, documentary, descriptive, correlational and explanatory, concluding that if there is responsability of the Nation, it must analyze each especific case in particular.
Keywords: human rights; covid-19; compensation for death